Revealing stakeholders' perspectives on educational language policy in higher education through Q-methodology. Issue 4 (7th August 2020) - Alkhateeb, Hadeel; Al Hamad, Muntasir; Mustafawi, Eiman
ABSTRACT: Qatar University is currently at a crossroads, having to respond to competing institutional, national, and international language policy issues. This paper aims to reveal how Qatar University's internal and external stakeholders perceive the future directions of the university's language in education policy. In particular, through Q-methodology, we attempt to uncover social perspectives on three educational language policy options, proposed to the university's higher administration, by the strategic planning team, to respond to pressing linguistic needs and priorities. The aim is to initiate and support a more-informed discussion about language in education policy at Qatar University. Results indicate strong agreement among the various perspectives taken by the university's stakeholders regarding the need for a language in education policy that seeks to manage the relationship between Arabic and English in a parallel way.